Pancasila as The Code of Conduct Paradigm (Comparative Study of National Education And Islamic Studies): PANCASILA SEBAGAI PARADIGMA KODE ETIK (Studi Banding Pendidikan Nasional Dan Kajian Islam) - Wasehudin, Wasehudin (Halaqa: Islamic Education Journal, 2020)
The undermined to Pancasila, as the final basic and the only Indonesia five fillars, always comes on behalf of a certain religious. This legitimates a certain purpose of those who are neither responsible or unappreciated to the independency of Republic of Indonesia lays form Sabang to Marouke. Pancasila as this national basis of Indonesia owns two dimensions; firstly, pancasila must develop mission and values of Godness as it is derived from first pillar. Secondly, Pancasila has its human dimension or human touch at which this dimension derived from second until fifth pillar, at which the national characters runs on and create justice and prosperious of the nation. These constitute the highest value of Pancasila in creating Indoensia human resource. It is the same as how Islamic education values at which ‘akhlak’, good characters (In English) as the basic pillar of Nabi Muhammad SAW as the God messenger that create the justice and social values. It is clear that Pancasila as code of conduct for both national education and Islamic education. Both drive through the same vision and mission to which as believed human being to God and those who have good characters as the main purposes of the both.